Wildfire preparedness and response during the 2016 Arouca wildfires in rural Portugal. (15th April 2022) - Asfaw, Henok Workeye; McGee, Tara K.; Correia, Fernando Jorge
Abstract: This study examined how residents living in rural Portugal were prepared for and took action to protect themselves and their property before and during the 2016 large Arouca wildfires. Interviews were completed with 30 residents living in small rural parishes affected by the wildfires. Qualitative research findings show that interview participants were aware of the high wildfire risk in the area but had different views about the source of risk and the immediate threat posed to their own property. During the wildfires, many participants reported taking last-minute preparatory actions such as having water, hoses, water pumps and sprinklers available. We found few differences in the preparatory roles carried out by women and men. Despite official evacuation recommendations, most participants stayed behind to protect their property. Participants' decisions to stay behind were affected by a feeling of confidence due to local knowledge and past experience, lack of trust in fire management agencies, and emotional attachment to their home and village. Participants were helped by family and village members, and in turn helped others during the wildfires. Recommendations for wildfire and emergency managers are discussed.